Protein intake and weight gain among low-income pregnant women from Mesquita County, Rio de Janeiro, Brazil - CABRAL, Maria; SICHIERI, Rosely; Medeiros Macedo da ROCHA, Camilla; Trindade de CASTRO, Maria Beatriz (Revista de Nutrição, 2023)
Objective To evaluate the effect of protein intake on body weight gain at pregnancy. Methods A cross-sectional study was carried out with 297 women who delivered a child at the maternity ward of Municipal Hospital Leonel de Moura Brizola in Mesquita city in the state of Rio de Janeiro. Sociodemographic and anthropometric data were collected through the use of a structured questionnaire at fi rst week after delivery. Food intake was assessed by a food frequency questionnaire. Protein intake per kilogram of body weight (g/kg per day) during pregnancy was categorized as high or low protein intake according to overall medianlevels. Hierarchical multiple linear regression was fitted to estimate the effect of protein intake per kg during pregnancy on weight gain. Results Women presented an average weight gain of 12.8kg (SD=6.34) and 26.8kg/m2 (SD=4.78) of Body Mass Index. Those who consumed a diet with high levels of protein content significantly presented less weight at postpartum (p<0.01) lower Early-Pregnancy Body Mass Index (p<0.01). In the hierarchical linear regression, it was found a negative association of protein intake per kg and Weight gain (b=-4.3025; IC95%=-6.0215; -2.5836; p<0.01). In the final model, all others covariates (energy, schooling, family income and gestational age) were significantly associated with the outcome (p<0.05). The additional model showed a negatively association between Early-Pregnancy Body Mass Index and weight gain (b=-0.2951; IC95%= -0.4987; -0.0915; p<0.01). Conclusion Higher levels of protein intake per kg of body weight during pregnancy were associated with lower weight gain.